α2* Nicotinic acetylcholine receptors influence hippocampus-dependent learning and memory in adolescent mice - Lotfipour, Shahrdad (2017)
The absence of α2* nicotinic acetylcholine receptors (nAChRs) in oriens lacunosum moleculare (OLM) GABAergic interneurons ablate the facilitation of nicotine-induced hippocampal CA1 long-term potentiation and impair memory. The current study delineated whether genetic mutations of α2* nAChRs (Chrna2L9′S/L9′S and Chrna2KO) influence hippocampus-dependent learning and memory and CA1 synaptic plasticity. We substituted a serine for a leucine (L9′S) in the α2 subunit (encoded by the Chrna2 gene) to make a hypersensitive nAChR. Using a dorsal hippocampus-dependent task of preexposure-dependent contextual fear conditioning, adolescent hypersensitive Chrna2L9′S/L9′S male mice exhibited impaired learning and memory. The deficit was rescued by low-dose nicotine exposure. Electrophysiological studies demonstrated that hypersensitive α2 nAChRs potentiate acetylcholine-induced ion channel flux in oocytes and acute nicotine-induced facilitation of dorsal/intermediate CA1 hippocampal long-term potentiation in Chrna2L9′S/L9′S mice. Adolescent male mice null for the α2 nAChR subunit exhibited a baseline deficit in learning that was not reversed by an acute dose of nicotine. These effects were not influenced by locomotor, sensory or anxiety-related measures. Our results demonstrated that α2* nAChRs influenced hippocampus-dependent learning and memory, as well as nicotine-facilitated CA1 hippocampal synaptic plasticity.